2020
DOI: 10.3390/ijms21051579
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Anti-Oxidative Activity of Indole-3-Acetic Acid Involves Induction of HO-1 and Neutralization of Free Radicals in RAW264.7 Cells

Abstract: The cellular and molecular mechanisms by which indole-3-acetic acid (IAA), a tryptophan-derived metabolite from gut microbiota, attenuates inflammation and oxidative stress has not been fully elucidated. The present study was to unearth the protective effect and underlying mechanism of IAA against lipopolysaccharide (LPS)-induced inflammatory response and free radical generation in RAW264.7 macrophages. IAA significantly ameliorated LPS-induced expression of interleukin-1β (IL-1β), interleukin-6 (IL-6), and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 37 publications
0
33
0
1
Order By: Relevance
“…[90][91][92][93] Similarly, IAA has been linked to the reduction of inflammation in hepatocytes and macrophages, as well as the prevention of nonalcoholic fatty liver disease. 94,95 These observations suggest that diseases other than IBD may in fact be dependent on gut microbiota-derived metabolites, a concept supported by correlative studies that identify co-morbidity between IBD and extra-intestinal inflammatory disorders such as asthma and rheumatoid arthritis. 96,97 Future studies might consider the hypothesis that the manipulation of the gut microbiota and/or its metabolites may be a unified means of addressing varied inflammatory disorders.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…[90][91][92][93] Similarly, IAA has been linked to the reduction of inflammation in hepatocytes and macrophages, as well as the prevention of nonalcoholic fatty liver disease. 94,95 These observations suggest that diseases other than IBD may in fact be dependent on gut microbiota-derived metabolites, a concept supported by correlative studies that identify co-morbidity between IBD and extra-intestinal inflammatory disorders such as asthma and rheumatoid arthritis. 96,97 Future studies might consider the hypothesis that the manipulation of the gut microbiota and/or its metabolites may be a unified means of addressing varied inflammatory disorders.…”
Section: Discussionmentioning
confidence: 92%
“…IPA specifically has been previously assessed for its roles in ameliorating neurodegenerative disorders (such as Alzheimer's Disease) and chronic kidney disease 90‐93 . Similarly, IAA has been linked to the reduction of inflammation in hepatocytes and macrophages, as well as the prevention of nonalcoholic fatty liver disease 94,95 . These observations suggest that diseases other than IBD may in fact be dependent on gut microbiota‐derived metabolites, a concept supported by correlative studies that identify co‐morbidity between IBD and extra‐intestinal inflammatory disorders such as asthma and rheumatoid arthritis 96,97 .…”
Section: Discussionmentioning
confidence: 99%
“…Study on rats revealed that IPA facilitated the protection against steatohepatitis induced by high-fat diet, as demonstrated by the improvement of gut dysbiosis and intestinal epithelial barrier function and the inhibition of pro-inflammatory signaling [118]. In addition, it has been shown that IAA displays anti-oxidative and anti-inflammatory activity, which is beneficial in the resistance to NAFLD induced by high-fat feeding and pro-inflammatory response in macrophages [119,120]. Interestingly, Bifidobacterium strains collected from human infants have been turned out to produce ILA [121], the favorable effect of these strains may be associated with ILA, which deserves to be corroborated in future studies.…”
Section: Functional Amino Acids (L-tryptophan and L-glutamine)mentioning
confidence: 99%
“…Cytokine array analysis revealed that miR-154-5p was necessary for the expression of MCP1 increased by antigen stimulation (Figure 4A). ROS production contributes to an increased expression of MCP1 (34). OVA-induced allergic airway inflammation is also closely associated with the increased expression of MCP1 (35).…”
Section: Discussionmentioning
confidence: 99%